Perceptual and Biochemical Responses in Relation to Different Match-Day +2 Training Interventions in Soccer Players - Trecroci, Athos; Perri, Enrico; Lombardi, Giovanni; Banfi, Giuseppe; Del Vescovo, Riccardo; Rosa, Ermes M.; Alberti, Giampietro; Iaia, F. Marcello (Frontiers in Physiology, 2021)
The aim of this study was to examine the impact of two different post-match training interventions on the subsequent recovery of perceptual and biochemical parameters after the game. In a crossover design, eight sub-elite players underwent a soccer-specific training (SST) and an active recovery regimen (AR) on the second day after a match (+48 h). Muscle soreness as well as muscle damage (creatine kinase, CK), inflammatory (C-reactive protein, and interleukin 6), immunological (e.g., lymphocytes, neutrophils, and monocytes) and endocrine (cortisol) markers were obtained at baseline (-72 h), immediately after (0 h) and 72 h post-match (+72 h). AR promoted a higher restoration of soreness values (P = .004, η2p = .49) together with a better restoration of CK within 72 h post-match compared with SST (P = .04, η2p = .36). Conversely, no significant (P > .05, η2p < .91) differences were observed in the recovery timeframe of inflammatory, immunological, and endocrine responses between SST and AR. Overall, AR elicited a quicker muscle soreness and CK restoration compared to SST intervention at 72 h post-match. Such information provides novel evidence-based findings on the appropriateness of different recovery strategies and may aid to improve the practitioners’ decision-making process when two consecutive games are played within 3 days.